PENGARUH PEMBERIAN AIR SEDUHAN BERAS YANG DIFERMENTASI OLEH MONASCUS PURPUREUS (ANGKAK) TERHADAP PENURUNAN KADAR KOLESTEROL SERUM PADA TIKUS PUTIH - Adhimass Wicaksono; Retno Sintowati; Sa’idatul Fitriyah (Biomedika, 2014)
The using of plant-based medicine is a popular approach to health care. A study presented by American Hearth Association showing that brown rice can lower cholesterol level in bood serum. To know the benefi ts of Angkak’s steeping water to decrease serum cholesterol levels in mice and determine the effects of Angkak’s steeping water to decrease serum cholesterol levels in rats compared with simvastatin. This study used an experimental research design, and using pre and post test control group design, performed in the laboratory of biomedical III FK UMS on November 1, 2012 to date of January 1, 2013. The purposive sampling technique, sampel determinaton using formula Federer by the number of sample of 30 male white rats wistar strain. After the data is collected, analyzed using the Shapiro-Wilk test, ANOVA, LSD, and the unpaired t test. The result of this study demnstrate hypothesis testing using ANOVA test with signifi cant level 95% of the negative control group, the treatment group a dose of 1, 2, and 3, it was found p0,05 were signifi cantly different meaning. In the test dose of LSD between treatment groups 2 and 3 the value of p=0,839 (p0,05) wich means no signifi cant difference. In the unpaired T test between the treatment group a dose of 1, 2, and 3 with positive control group were signifi cant difference. The unpaired T test between the treatment group a dose of 1, 2, and 3 with white rice also found signifi cant difference. Conclusion: Angkak’s steeping water can lower serum cholesterol levels of white rat as well as the water steepimg Angkak has the same effectiveness with simvastatin to decrease serum cholesterol levels of mice.Keyword: Cholesterol, Angkak